KONSEP DAYA TAMPUNG RUANG TERBUKA PUBLIK PASCA PANDEMI COVID-19 (Studi Kasus: Taman Balai Kota Bandung) - Nurwulandari, Furi Sari; Rismana, Gerry Andrika; Syarifudin, Deden; Septiani, Aulia Irina (Universitas Galuh, 2023)
The emergence of the Covid-19 pandemic has changed the pattern and form of activities in the use of public spaces in general. The community experiences difficulties in the process of carrying out social activities, such as setting distance in interactions and setting limited operating hours for activities. For this reason, infrastructure supporting activities and health protocol rules that must be carried out before and after activities are important in a structured size and concept as adaptive solutions in social and economic activities for the community. Each city needs to manage its own public space independently and must also be able to ensure rules that are easily applied by all people in carrying out activities in public spaces in an inclusive manner. In this context, the availability of public spaces and activity tools that guarantee safety and comfort are one of the main tools in preparing a spatial structure plan that complies with health protocols to mitigate the risk of the Covid-19 pandemic. The purpose of this study was to determine the capacity of public open space in the form of a city park with the Bandung City Hall Park study locus, as well as the elements contained in a city park in accordance with the Covid-19 pandemic-free health protocol approach. The research method used is a qualitative and quantitative descriptive approach. The expected output of this research is the concept of planning the capacity of public open spaces in the form of city parks by considering post-Covid-19 pandemic conditions.